Peningkatan Pemahaman Bencana Alam Pada Anak Melalui Teknik Bermain Sains Sederhana - Laini, Riza (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2020)
The purpose of this research is to improve children's understanding of natural disasters. The subjects of this study were 20 children of Group B, all of whom were girls. This research was conducted in two cycles, where each cycle consisted of three meetings. Data collection techniques using test techniques, observation techniques, and documentation techniques. From the learning process in the first cycle obtained an average value of 1.8 with a percentage level of 61.4% in the sufficient category and increased in the second cycle to 2.41 with a percentage of 80.3%. Based on the results of the research, it can be argued that there was an increase in the ability to understand natural disasters in group B children through simple science playing techniques in Raudhatul Athfal Rabbi Radhiyya Curup